Effects of cavitation on different microorganisms: The current understanding of the mechanisms taking place behind the phenomenon. A review and proposals for further research - Zupanc, Mojca; Pandur, Žiga; Stepišnik Perdih, Tadej; Stopar, David; Petkovšek, Martin; Dular, Matevž (Ultrasonics sonochemistry, 2019)
[Display omitted] •A focused and critical review of publications from the last decade was made.•Cavitation shows great potential to destroy various microorganisms and viruses.•We point to many inconsistencies in reported results.•Recommendations that need to be followed in order to progress the filed are given. A sudden decrease in pressure triggers the formation of vapour and gas bubbles inside a liquid medium (also called cavitation). This leads to many (key) engineering problems: material loss, noise, and vibration of hydraulic machinery. On the other hand, cavitation is a potentially useful phenomenon: the extreme conditions are increasingly used for a wide variety of applications such as surface cleaning, enhanced chemistry, and wastewater treatment (bacteria eradication and virus inactivation). Despite this significant progress, a large gap persists between the understanding of the mechanisms that contribute to the effects of cavitation and its application. Although engineers are already commercializing devices that employ cavitation, we are still not able to answer the fundamental question: What precisely are the mechanisms how bubbles can clean, disinfect, kill bacteria and enhance chemical activity? The present paper is a thorough review of the recent (from 2005 onward) work done in the fields of cavitation-assisted microorganism’s destruction and aims to serve as a foundation to build on in the next years.